(untitled) (Thành Phố Hồ Chí Minh, 1993)
Contents of volume 1: Contains 10 papers about the common problems of the project and about the basic physical-chemical processes.
Keywords: Acid sulfate soils,Water-supply, Agricultural; Management,Simulation methods